Surface hydrochemical dynamic in an artificial lake with anthropic impact: La Purísima reservoir, Central Mexico - Lecomte, Karina Leticia (2022)
In the present study, the hydrochemical dynamic and the water quality of La Purísima reservoir, Central Mexico, have been determined. The reservoir presents total dissolved solids (TDSs) between 146 and 328 mg L−1 and water quality neutral to slightly alkaline (pH 7.0 to 8.7) during the dry season, whereas it becomes clearly alkaline (pH 8.1–9.9) in the rainy-warm season. Through its main tributaries, La Purísima reservoir has been receiving water affected by anthropic activities, such as mining, urbanization, and agriculture. La Purísima reservoir indicates water quality suitable for irrigation and aquatic lives, but unsuitable for drinking purposes. A geochemical evolution from the riverine to the lacustrine zone is evidenced by the complexation of several free ions: the higher saturation indexes; the lower toxic metal concentrations; and the lower trophic status, which ameliorate the water quality in the lacustrine zone. Trace elements co-precipitate and are adsorbed onto bottom sediments. During summer, high evaporation rates and atmospheric precipitation are found to decline the water quality. Cluster analyses reflect the geo-setting and different pollution levels: urban impact from the north coast, and agricultural activities from the east coast. The sensitivity of the lake to geochemical behavior can be used to understand the complex dissolved geochemical dynamics in a lake and the potential effects from long-term anthropic impact variability. The information about water quality of La Purísima reservoir may be useful to preserve the ecosystem and its biodiversity.